Kadar Asam Urat Penderita Tuberkulosis Sebelum dan Sesudah Mengkonsumsi Obat Anti Tuberkulosis di Rumah Sakit X - Mega Pratiwi Irawan (Akademi Kesehatan John Paul II Pekanbaru, 2021)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Treatment of tuberculosis contained at least four types of drugs such as Rifampicin, Ethambutol, Streptomycin and Pyrazinamide. Ethambutol and Pyrazinamide can cause an increase in uric acid levels. This study aims to describe the uric acid levels of tuberculosis patients of Rumah Sakit X. This type of research was Cross Sectional by taking secondary data on the patient's medical record at Rumah Sakit X. The results of laboratory tests from 20 tuberculosis patients who consumed anti tuberculosis drugs showed that uric acid levels above normal after taking the drug for 2 months was suffered by 5 male patients (25%) and 7 female patients (35%). Uric acid levels above normal was suffered by 4 male patients (20%) and 7 female patients (35%) after taking the drug for 4 months. Uric acid levels above the normal was suffered by 4 male patients (20%) and 6 female patients (30%) after taking the drug for 6 months. By using ANOVA test, get t count 0,000 <0,005. The conclusion of this study is that there is a difference between uric acid levels before treatment and after treatment.